(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The vision of higher education in India is to realize the country’s human resources potential to its fullest with equity and inclusion. The higher education sector, in recent decades, has witnessed a tremendous growth in many aspects such as its institutional capacity, enrolment, teacher-student ratio, etc. The rapid expansion of the higher education system at the same time has brought several pertinent issues related to equity, efficiency, excellence and access to higher education in the country. The present paper holds an immediate significance of creating awareness of many issues of concern to be taken care of by the stakeholders in the national as well as the global levels. The study is also unique in the sense that it brings about better understanding of the present scenario in the higher education system in the country and its pattern of growth given the opportunities and challenges to the system under consideration. The present study throws a gainful insight on financing schemes and enrolment aspects of higher education in India.